Enhancing Active Learning Through Gamified Platforms: Insights from the Implementation of Quizizz in English Language Education - Khayrullah, Nur Fitrawan; Jabri, Umiyati; Samad, Ita Sarmita; Hasan, Hasan (Majesty Journal, 2024)
This study investigates the impact of the Quizizz application on English vocabulary mastery among eighth-grade students at MTs. DDI Enrekang. As education enters the digital age, integrating technology into classrooms has become essential. This research employs a pre-experimental design with a one-group pre-test and post-test structure to evaluate the efficacy of Quizizz in enhancing students’ vocabulary proficiency. The study involved 34 students, using total population sampling to ensure comprehensive analysis. The results indicate a significant improvement in students’ vocabulary mastery, with post-test scores showing considerable increases compared to pre-test scores. Descriptive statistics reveal a rise in the mean score from 47.21 to 73.53, while inferential statistics confirm the significance of these improvements. The study highlights the effectiveness of Quizizz in fostering student engagement and motivation through its interactive and gamified features. The findings suggest that gamified platforms like Quizizz can transform traditional learning environments, particularly in rural settings with limited access to advanced tools. This research contributes to the growing body of knowledge on the benefits of gamification in education and underscores the potential for such tools to enhance language learning outcomes. Future research could explore the long-term effects of gamified learning and its applicability across various subjects and educational contexts.